(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2008)
Calcareous nannofossil biostratigraphic investigations have been carried out on samples collected from the Tabiago section, Brianza, northern Italy. This section records early Maastrichtian (CC23b nannofossil zone) to early Eocene (NP10 nannofossil zone) calcareous nannofossil assemblages. The Cretaceous-Tertiary transition is characterized by major changes in sedimentation rates and two likely stratigraphic gaps. The Cretaceous Brenno Formation was deposited with a high sedimentation rate ( 20 m/m.y.), whilst the Tabiago Formation of Paleogene age records a drastic decrease ( 10 m/m.y.). The absence of the CC26 zonal marker Micula prinsii may indicate a stratigraphic hiatus or an extremely condensed level in the latest Maastrichtian. However, only two samples have been collected and analyzed in this interval due to low exposure of the outcrop, and the absence of M. prinsii could be the result of diagenetic overprint or insufficient sampling. A stratigraphic hiatus or a very condensed interval corresponds to the upper part of NP1 nannofossil zone and PƒÑ foraminiferal Zone and P1a Subzone in the early Paleocene. The poor exposure of the outcrop prevents to precisely locate the zonal boundaries between NP4 and NP5 and between NP9 and NP10 and impedes the documentation of possible further stratigraphic gaps or condensed intervals.